The Impact of Banking Governance Principles on the Enhancement of Financial Report Quality: A Field Study on Employee Perspectives at the Bank of Baghdad - Salah Awad Mohamed; Khaled Aziz Farhan (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This study focuses on key subjects within the banking industry, specifically banking governance and the integrity of financial reports. The objective of this study was to provide a comprehensive analysis and explanation of the theoretical and scientific consequences associated with these variables. The study is bifurcated into two primary sections: the initial section delineates the research technique and the conceptual framework of the research variables. Regarding the subsequent section, it explores the analytical framework of the study hypotheses, together with its findings and suggestions. The objective of this study was to examine the impact of banking governance principles on the improvement of financial reporting quality, as perceived by a selected group of Bank of Baghdad staff. The achievement of this study involved the examination of the linkages and effects between the variables under investigation, namely banking governance and financial report quality. The study employed a descriptive-analytical technique, with a sample size of 73 individuals. A questionnaire was utilized as the measurement tool. The research hypotheses pertaining to the correlation and influence of the research variables were validated using statistical analysis using SPSS. This analysis involved the utilization of multiple regression and correlation coefficients. The research findings highlight the paramount importance of banking governance principles in enhancing the performance of financial institutions, specifically banks. These principles are crucial in effectively managing banking operations and ensuring optimal monitoring. The research findings suggest that the study offers a number of recommendations. One such proposal is for bank management to prioritize banking governance principles and implement them in order to attain the bank's objectives, as outlined in the study.